Manual on fishermen's cooperatives - Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization, 1971)
This examines the principles underlying the management of fishermen's cooperatives. It also highlights different aspects and stages of cooperatives management and administration.
Includes bibliographical references: p. [119]-124.
asm 24/01/2019
Loans
Keywords: Fisheries, Cooperative; Cooperatives